Understanding the landscape of national policies and strategic plans to tackle undernutrition in India: a review - Vir, Sheila; Sreenath, K.C.; Vose, Vijay; Chauhan, Kavita; Mathur, Shivani; Menon, Subhadra (International Food Policy Research Institute, 2013)
In India, 46 percent of infants and children under 3 years old are underweight and more than two-thirds are anemic (MHFW 2006). This is despite substantial economic growth and multiple policies developed over several decades to support diverse actions to tackle undernutrition. The Indian response to tackling undernutrition must focus on the most effective strategies and interventions to ensure rapid improvement. Toward this end, the effective and efficient mobilization of evidence is critical. This paper presents key findings from a policy review led by a team from the Public Health Foundation of India that documented the use of evidence in nutrition policymaking and planning in India and the facilitators of and barriers to its use.